173k views
0 votes
I need the answer fore both plsss

I need the answer fore both plsss-example-1
User Tarique
by
5.5k points

1 Answer

5 votes

Answer: 6i) 6a² - 2ab

6ii) -2b³

6iii) b³ + 7b² - 49b

Explanation:

6i) (a + b)(5a - 3b) + (a - 3b)(a - b)

= 5a² - 3ab + 5ab - 3b² + a² - ab - 3ab + 3b²

= 5a² + 2ab - 3b² + a² - 4ab + 3b²

= 6a² - 2ab

6ii) (a - b)(a² + b² + ab) - (a + b)(a² + b² - ab)

= a³ + ab² + a²b - ab² - a²b - b³ - (a³ + ab² - a²b -ab² + a²b + b³)

= a³ - b³ - (a³ + b³)

= a³ - b³ - a³ - b³

= -2b³

6iii) (b² - 49)(b + 7) + 343

= b³ + 7b² - 49b - 343 + 343

= b³ + 7b² - 49b

You are allowed a maximum of 3 questions.

Please post #7 on a different question.

User Noir
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.